Some aspects of the Kazakh-British economic cooperation (International relations and international law Journal, 2016)
Within a framework of the concept of multi-vector foreign policy of the Republic of Kazakhstan much attention and importance is given to the European vector. One of the key partners of Kazakhstan in Europe initially was the United Kingdom. At the dawn of sovereignty exactly the British Prime Minister Margaret Thatcher was the first foreign head of state who visited the former Soviet republic. Currently, the UK is part of the so-called «trillion» economies in the world, ranks third in terms of direct investments in projects in Kazakhstan. According to Ambassador Extraordinary and Plenipotentiary of Great Britain in the Republic of Kazakhstan Mr. Paul Brummell: «Among 27 EU member states in particular UK is a trade and economic partner number one for Kazakhstan. We must build more complete relationship that will reflect the level of the economic cooperation. « The basis of the bilateral relations are oil, gas and cooperation in the financial sector. British investments in Kazakhstan’s economy are growing, the numbers of Kazakh companies which place its shares on the London Stock Exchange are increasing.
Keywords: multi-vector; the European vector; trade and economic cooperation; direct investments; financial sector; joint ventures